2020
DOI: 10.1177/1538574420966106
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Aortic Mural Thrombus, Right Ventricular Clot and Pulmonary Embolism in a Patient With COVID-19 Pneumonia

Abstract: Since the outbreak of the COVID-19 pandemic, increasing evidence suggests that infected patients present a high incidence of thrombotic complications. We report a 67-year-old-woman admitted for severe acute respiratory syndrome coronavirus 2 infection. Chest CT images showed bilateral ground glass opacities, bilateral pulmonary embolism, right ventricular clot in transit and 2 thoracic aortic mural thrombus. Therapy was initiated with subcutaneous low-molecular-weight heparin, and the patient was discharged at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A total of 55 patients from the database research and 1 patient from our facility were included. 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 Of the included studies, 12 were case series and 26 were case reports. Essential characteristics of the included patients are outlined in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 55 patients from the database research and 1 patient from our facility were included. 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 Of the included studies, 12 were case series and 26 were case reports. Essential characteristics of the included patients are outlined in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review revealed thirty articles (17 case reports/series, 9 letters-to-journal-editors, 3 brief clinical imaging reports, and 1 retrospective study) detailing 52 SARS-CoV-2-positive patients with acute aortoiliac arterial thrombosis 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 . The available information from these cases were compiled and analyzed in addition to our institution's 7 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Since the beginning of the pandemic, most reports on thrombotic complications have focused on the problem of deep vein thrombosis and pulmonary embolism [ 19 , 20 , 21 ]. Although thrombus formation within the right atrium, right ventricle can lead to consecutive pulmonary embolism, this issue is under-reported in the scientific literature and clinical guidelines [ 22 , 23 , 24 , 25 ]. There are also few data on aortic thrombosis in COVID-19 and its combination with venous thrombosis [ 24 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%